2021
DOI: 10.1002/onco.13956
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of Early-Stage Cervical Cancer with Intermediate-Risk Factors: Model Development and Validation Based on Machine Learning Algorithm

Abstract: Background. Adjuvant therapy for cervical cancer (CC) patients with intermediate-risk factors remains controversial. The objectives of the present study are to assess the prognoses of early-stage CC patients with pathological intermediate-risk factors and to provide a reference for adjuvant therapy choice. Materials and Methods. This retrospective study included 481 patients with stage IB-IIA CC. Cox proportional hazards regression analysis, machine learning (ML) algorithms, Kaplan-Meier analysis and the area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…On the contrary, based on the traditional Sedlis criteria 38 as the risk classification system, no significant difference in OS was observed within the cohort. 39 Promising results incorporating ML algorithms with gene expression, molecular subtyping, and pharmacogenomics in CC patients were also reported recently. 40 , 41 , 42 …”
Section: Discussionmentioning
confidence: 95%
“…On the contrary, based on the traditional Sedlis criteria 38 as the risk classification system, no significant difference in OS was observed within the cohort. 39 Promising results incorporating ML algorithms with gene expression, molecular subtyping, and pharmacogenomics in CC patients were also reported recently. 40 , 41 , 42 …”
Section: Discussionmentioning
confidence: 95%
“…They emphasized that LVSI was the only independent prognostic factor. On the contrary, when the criteria were examined in more detail, Chu et al ( 15 ) reported on the validation of risk stratification using a machine learning algorithm in addition to the Sedlis criteria. This risk stratification consisted of age, LVSI, stromal invasion, size and type of adjuvant therapy, and was able to indicate expected OS and disease-free survival (DFS) 2 and 5 years after surgery ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, when the criteria were examined in more detail, Chu et al ( 15 ) reported on the validation of risk stratification using a machine learning algorithm in addition to the Sedlis criteria. This risk stratification consisted of age, LVSI, stromal invasion, size and type of adjuvant therapy, and was able to indicate expected OS and disease-free survival (DFS) 2 and 5 years after surgery ( 15 ). These expected OS and DFS rates were derived based on the time-dependent receiver operating characteristic (ROC) curves and the area under the ROC curve.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [ 50 ] in 2020 found that pretreatment albumin to fibrinogen ratio was significantly related to lymph node metastasis, depth of stromal infiltration, etc. Many studies focused on prediction for survival outcomes or a single PRF of cervical cancer based on clinical factors [ 51 , 52 , 53 ] and/or radiomic parameters [ 54 , 55 ]. However, no studies have made an attempt to predict three PRFs based on a series of clinically readily available blood markers.…”
Section: Discussionmentioning
confidence: 99%